Identifikasi Cendawan Penyebab Bercak Daun Pokem (Setaria italica L.) - Willem Awom; Derek Kornelis Erari; Frangky Arthur Paiki (Agrotek, 2015)
This research aimed to identify the type of fungus that causes the appearance of spots on the leaves of pokem. Descriptive method were used in this research with laboratory observation technique which consisted by preparation, sampling of pokem leaf, isolation, purification, innoculation and the observation of pathogen character. The result showed that the pathogen causing pokem (Setaria italica L.) leaf spot was a fungal pathogen Cercospora jenseana, f. Sp. Setariae which can be seen from the symptoms of the plant through the koch postulate test and the identification of color, shape and character of the colony, mycelium, hyphae, and spores.